Visual Storytelling: Unlearning Gender Stereotyping Inside Classroom - Dhungel, Anita (Journal of NELTA, 2016)
This paper introduces ‘stereotype’, ‘prejudice’, and ‘discrimination’, and points out that the three revolve around and remain in a vicious association. Many stereotypical presentations found in educational materials have been explored in the article. the author has stressed the need for developing the qualities of compassion, tolerance, respect for individuals, and preserving their identity through education—so that stereotyping or discriminatory acts can be avoided altogether. Journal of NELTA, Vol. 21, No. 1-2, 2016, Page: 11-22